2021
DOI: 10.2166/wcc.2021.174
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of CFSR, MERRA-2 and TRMM3B42 data sets in simulating river discharge of data-scarce tropical catchments: a case study of Manafwa, Uganda

Abstract: Data scarcity has been a huge problem in modelling various catchments especially in the tropical region. Satellite data and different statistical methods are being used to improve the quality of conventional meteorological data. However, the potential of using these data needs to be further investigated. This paper evaluates the performance of three reanalysis datasets in hydrological modelling of the Manafwa Catchment, Uganda. Two reanalysis datasets were selected for studying both rainfall and temperature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To train the deep learning model, monthly average meteorological data that were taken from the MERRA-2 dataset include surface temperature, wind speed, specific humidity, planetary boundary layer height (PBLH), and sea level pressure, as these parameters can strongly influence the PM 2.5 concentration . Several studies have compared the MERRA-2 dataset with ground-based observations and other reanalysis datasets, and results showed that the MERRA-2 data are able to represent the surface meteorological conditions. , The performance of MERRA-2 on temperature, relative humidity, wind speed, PBLH, and sea level pressure is summarized in Table S1. For example, when compared with the ground observation data from China, the RMSE, mean bias (MB), and R values for temperature were 3.62 K, −2.14 K, and 0.95, respectively .…”
Section: Methodsmentioning
confidence: 99%
“…To train the deep learning model, monthly average meteorological data that were taken from the MERRA-2 dataset include surface temperature, wind speed, specific humidity, planetary boundary layer height (PBLH), and sea level pressure, as these parameters can strongly influence the PM 2.5 concentration . Several studies have compared the MERRA-2 dataset with ground-based observations and other reanalysis datasets, and results showed that the MERRA-2 data are able to represent the surface meteorological conditions. , The performance of MERRA-2 on temperature, relative humidity, wind speed, PBLH, and sea level pressure is summarized in Table S1. For example, when compared with the ground observation data from China, the RMSE, mean bias (MB), and R values for temperature were 3.62 K, −2.14 K, and 0.95, respectively .…”
Section: Methodsmentioning
confidence: 99%